P168Anti-hypercholesterolemic effect of a preparation of vitamins, minerals and trace elements in experimental hyperlipidemia. (15th July 2014) - Sarkozy, M; Szucs, G; Szucs, CS; Barkanyi, J; Bencsik, P; Gaspar, R; Csonka, CS; Konya, CS; Ferdinandy, P; Csont, T
Abstract: Although multivitamin products are widely used as dietary supplements, the effects of these products were not investigated in hypercholesterolemia which is a major risk factor of cardiovascular diseases. Therefore, here we investigated if a preparation of different minerals, vitamins, phytosterols and trace elements (MVT) developed for human use affects the severity of experimental hyperlipidemia as well as myocardial ischemia/reperfusion injury. Male Wistar rats were fed a normal or a 2% cholesterol plus 0.2% cholic acid-enriched diet for 12 weeks to induce hyperlipidemia. From week 8, rats in both groups were fed with an MVT preparation or placebo for 4 weeks. Serum triglyceride and cholesterol levels were measured at week 0, 8 and 12. At week 12, hearts were isolated, perfused according to Langendorff and subjected to a 30-min coronary occlusion followed by 120 min reperfusion. At week 8, cholesterol plus cholic acid-fed rats showed significantly higher serum cholesterol level as compared to normal rats, however, serum triglyceride level did not change. At week 12, MVT treatment significanty decreased serum cholesterol level in the hyperlipidemic group, however, MVT treatment failed to decrease infarct size in the hyperlipidemic hearts. In the normolipidemic group, MVT treatment did not influence the serum cholesterol level or the infarct size. We conclude that MVT treatment reduces serum cholesterol level in hyperlipidemia, however, it fails to decrease infarct size.